Microbially derived surfactants: an ecofriendly, innovative, and effective approach for managing environmental contaminants - Singh, Navdeep; Hu, Xiao-Hu; Kumar, Vikash; Solanki, Manoj Kumar; Kaushik, Amit; Singh, Vipin Kumar; Singh, Sandeep Kumar; Yadav, Priya; Singh, Rahul Prasad; Bhardwaj, Nikunj; Wang, Zhen; Kumar, Ajay (Frontiers in Bioengineering and Biotechnology, 2024)
The natural environment is often contaminated with hydrophobic pollutants such as long-chain hydrocarbons, petrochemicals, oil spills, pesticides, and heavy metals. Hydrophobic pollutants with a toxic nature, slow degradation rates, and low solubility pose serious threats to the environment and human health. Decontamination based on conventional chemical surfactants has been found to be toxic, thereby limiting its application in pharmaceutical and cosmetic industries. In contrast, biosurfactants synthesized by various microbial species have been considered superior to chemical counterparts due to their non-toxic and economical nature. Some biosurfactants can withstand a wide range of fluctuations in temperature and pH. Recently, biosurfactants have emerged as innovative biomolecules not only for solubilization but also for the biodegradation of environmental pollutants such as heavy metals, pesticides, petroleum hydrocarbons, and oil spills. Biosurfactants have been well documented to function as emulsifiers, dispersion stabilizers, and wetting agents. The amphiphilic nature of biosurfactants has the potential to enhance the solubility of hydrophobic pollutants such as petroleum hydrocarbons and oil spills by reducing interfacial surface tension after distribution in two immiscible surfaces. However, the remediation of contaminants using biosurfactants is affected considerably by temperature, pH, media composition, stirring rate, and microorganisms selected for biosurfactant production. The present review has briefly discussed the current advancements in microbially synthesized biosurfactants, factors affecting production, and their application in the remediation of environmental contaminants of a hydrophobic nature. In addition, the latest aspect of the circular bioeconomy is discussed in terms of generating biosurfactants from waste and the global economic aspects of biosurfactant production.